Analysis of the Impact of Process Automation and Human Resource Management on Production Completion Time and Product Quality in the Fast Food Industry in West Java - Mohammad Gifari Sono; Apriyanto Apriyanto; Ellys Nurhaliza (Westscience Press, 2024)
This study investigates the impact of process automation and human resource management (HRM) on production turnaround time and product quality in the fast food industry in West Java. Using a quantitative research design, data were collected from 180 respondents through a structured questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The findings reveal that both process automation and HRM significantly influence production turnaround time and product quality, with automation showing a stronger impact on quality and HRM demonstrating a more substantial effect on turnaround time. The study highlights the synergistic relationship between automation and HRM, emphasizing their combined role in achieving operational efficiency and maintaining high product standards. These results provide actionable insights for fast food businesses to integrate technological advancements with strategic human resource practices, ensuring competitiveness in a dynamic market.